Analysis of the factors influencing the career choice of undergraduate UMP students using analytical hierarchy process (AHP) - Faaris Assyifa, Radi (2014)
Students have to choose the right career after their graduates. In many case nowadays many fresh graduate get a job not really based on what courses their study in Higher Education College. It can be conclude that choosing the right career is a critical decision in a student’s life. Various aspect condition the decision of a students. This paper aim to analyse the factor that affect the career choices of undergraduate engineering and technology students. There are many possible factor that shaping the choices of students are listed based on previous study. The students of 3rd and ﬁnal year student of UMP Gambang campus surveyed. The survey ﬁnds that the most dominating career preference among the students is to be in Industrial and ﬁeld work. Using a decision making process name analytical hierarchy process. The relative weight of the various factors affecting this trend are found. The expected analysis for a majority of students, personal aptitude, growth prospects and future income are the most dominating factors in the decision making process. Long gestation period was the considered the least important but acceptable as long as more important factors like growth prospect, personal aptitude and future income are favourable in that career option. As the conclusion, this research may beneﬁt the higher education to identify the best development program or attitude motivation for the student as preparation and student may realise the most general factor affecting them in career choices after graduated. This research also may vary the result in the different higher education area as the UMP was a technical area university